2016
DOI: 10.1155/2016/8048170
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Inhibits Osteoclast Differentiation and Bone ResorptionIn Vitrovia Enhancing the Production of IL-10 and TGF-β1 by Regulatory T Cells

Abstract: Triptolide, a purified component of Tripterygiumwilfordii Hook F, has been shown to have immunosuppressive and anti-inflammatory properties in rheumatoid arthritis (RA). Although triptolide has demonstrated that it could suppress bone destruction in collagen-induced mice, its therapeutic mechanism remains unclear. Many studies have investigated the effect of triptolide on Tregs and Tregs-related cytokine involved in RA. Additionally, previous studies have implied that Tregs inhibit osteoclast differentiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 28 publications
(30 reference statements)
0
42
0
Order By: Relevance
“…Similarly, TL markedly suppressed the overexpression of CCR5 induced by AA. Recently, Xu et al (16) reported that TL inhibited osteoclast differentiation and bone resorption in rheumatoid arthritis, and the repressive effects of T-regulatory cells on bone resorption were enhanced by TL through promoting the secretion of transforming growth factor-β1 and IL-10. A study by Wei et al (19) indicated that TL retarded the Toll-like receptors (TLRs)/nuclear factor (NF)-κB signaling pathway to alleviate experimental colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, TL markedly suppressed the overexpression of CCR5 induced by AA. Recently, Xu et al (16) reported that TL inhibited osteoclast differentiation and bone resorption in rheumatoid arthritis, and the repressive effects of T-regulatory cells on bone resorption were enhanced by TL through promoting the secretion of transforming growth factor-β1 and IL-10. A study by Wei et al (19) indicated that TL retarded the Toll-like receptors (TLRs)/nuclear factor (NF)-κB signaling pathway to alleviate experimental colitis.…”
Section: Discussionmentioning
confidence: 99%
“…TL is known as a drug with marked pharmacological activities, including anti-inflammatory and immunomodulatory properties as well as improvement of the microcirculation; it inhibits the proliferation of various types of cancer cell and enhances tumor sensitivity to chemotherapy (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In the present study, the expression patterns of IL-6 in a mouse model of UC model were assessed, as well as association between the anti-colitis effects of TL and IL-6 levels.…”
Section: Introductionmentioning
confidence: 99%
“…So far, research focused on the effects of TwHf on Treg cells in RA were limited. In the co-culture system of bone marrow macrophages and Tregs, TP up-regulated IL-10 and TGF-β1 produced by Treg cells, resulting in the inhibition of osteoclast differentiation and bone resorption ( Xu et al., 2016 ).…”
Section: The Functions Of Tripterygium Ingredients On T Cells and Thementioning
confidence: 99%
“…In RA, osteoclasts formation and differentiation are closely associated with local bone erosion (Wei et al, ). The previous study has showed that IL‐10 and transforming growth factor‐β1, the cytokines secreted from regulatory T cells, play a key role in suppressing osteoclast differentiation and bone resorption (Xu et al, ). Triptolide enhances these suppressive effects by promoting the production of IL‐10 and transforming growth factor‐β1 (Xu et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
“…The previous study has showed that IL‐10 and transforming growth factor‐β1, the cytokines secreted from regulatory T cells, play a key role in suppressing osteoclast differentiation and bone resorption (Xu et al, ). Triptolide enhances these suppressive effects by promoting the production of IL‐10 and transforming growth factor‐β1 (Xu et al, ). The aryl hydrocarbon receptor participates in the activation and differentiation of osteoclasts (Wei et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%